8-Hydroxyquinoline derivatives with 2-pyrazoline fragment in chromophore system as chelating agents for polyvalent metals - Marrugo Gonzalez, A.J.; Orlov, V.D.; Doroshenko, A.O. (Functional Materials, 2008)
A group of compounds is described containing two connected structure fragments in molecules, the chelating 8-hydroxyquinoline and fluorescent aryl-2-pyrazoline. Such compounds may be of good prospects in chemical analysis as well as in medical and biological field. The study of absorption and fluorescence spectra of the initial compounds and their complexes with metal ions have shown a high sensitivity of the spectra to complexing process, thus suggesting their potential as chelating agents.